Genetic structure and demographic history of Northern Han people in Liaoning Province inferred from genome-wide array data - Zhou, Jingbin; Zhang, Xianpeng; Li, Xin; Sui, Jie; Zhang, Shuang; Zhong, Hua; Zhang, Qiuxi; Zhang, Xiaoming; Huang, He; Wen, Youfeng (Frontiers in Ecology and Evolution, 2022)
In this study, we used typical and advanced population genetic analysis methods (principal component analysis (PCA), ADMIXTURE, FST, f3‐statistics, f4‐statistics, qpAdm/qpWave, qpGraph, ALDER and TreeMix) to explore the genetic structure of 80 Han individuals from four different cities in Liaoning Province and reconstruct their demographic history based on newly generated genome-wide data. We found that the Liaoning Han people have genetic similarity with other northern Han peoples (Shandong, Henan and Shanxi) and Liaoning Manchu people. Millet farmers in the Yellow River Basin (YRB) and West Liao River Basin (57%-98%) and hunter-gatherers in the Mongolian Plateau and Amur River Basin (40%-43%) are the main ancestral sources of the Liaoning Han people. In general, our study further supports the “northern origin hypothesis”; YRB-related ancestry accounts for 83%-98% of the genetic makeup of the Liaoning Han population. There are obvious genetic influences of northern East Asian populations in the Liaoning Han people, ancient Northeast Asian-related ancestry is another dominant ancestral component, and large-scale population admixture occurred between the Tungusic Manchu and Han peoples. Interestingly, there are genetic differences among the Liaoning Han peoples, and we found that these differences are associated with different migration routes of Hans during the “Chuang Guandong” period in historical records.